HISTOPATHOLOGICAL STUDY OF SEPSIS EXPERIMENTALLY INDUCED BY CECAL LIGATION AND PUNCTURE IN RATS - A. M. Al-Saidya H. Kh. Ismail (Basrah Journal of Veterinary Research)
The aim of this study was to investigate the histopathological lesions in the liver,kidney and lung sections in rats with sepsis that experimentally induced by cecal ligation and puncture CLP procedure to induce intra-abdominal infection. It was found that CLP models leads to higher mortality rate comparisons to sham-operated and un– operated animals. Also there were severe lesions in the liver , kidney and lung of rats with sepsis , characterized by severe massive necrosis in hepatic cells , while the histopathological changes in kidney of CLP rats revealed severe glomerulonehritis with infiltration of inflammatory cells , in lung , severe interstitial and bronchial pneumonia , with presence of severe thickening of blood vessel wall with thrombi . In conclusion, the results of this study have demonstrated that CLP induces high mortality rate , an acute systemic septic state with multiple organ dysfunction especially the Liver , kidney and Lung based on histopathological observations . These features were not observed in sham - operated or un-operated rats .